ANALISIS EFEKTIVITAS KURIKULUM BERBASIS CINTA DALAM PEMBENTUKAN KARAKTER SISWA DI MADRASAH ALIYAH NEGERI - Ridho Dwi Putra; Ahmad Zainuri; Muslim Ghani Yasir (STKIP Subang, 2026)
Student character building is one of the primary goals of education in Indonesia, particularly in Islamic educational institutions such as State Islamic Senior High Schools (MAN). Effective character education focuses not only on cognitive aspects but also on students' affective and social aspects. One new approach introduced to support this goal is the Love-Based Curriculum (KBC), which places the values ​​of love, empathy, and respect as the main foundation of the learning process. This study uses literature review and theoretical studies to analyze the effectiveness of the KBC in shaping the character of MAN students, as well as the challenges and opportunities for its implementation in the context of Islamic education. The study results indicate that the KBC has the potential to improve character values ​​such as empathy, responsibility, discipline, and social goodness in students, although its implementation requires adequate policy support, teacher training, and affective evaluation.